1988
DOI: 10.1111/j.2044-8295.1988.tb02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Repetition and active listening: The effects of spacing self‐assessment questions

Abstract: This study is concerned with the practical application of repetition effects in a classroom setting. In Expt 1 subjects listened to a short passage. At various points in the passage they were required to answer a self-assessment question (SAQ) which referred to an item of information in the immediately preceding portion of the text. Each SAQ was then repeated either immediately, or after one minute, two minutes, or four minutes. Three hours later subjects were given an unexpected recall test in which they atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This suggests that more training keeps the listener on track, even if the design in the present study cannot answer whether this is an effect of enhanced RL skills or an unspecific effect of more role playing. A study of repetition and selfassessment of questions (Parkin, Wood, & Aldrich, 1988) showed that recall of orally presented information is influenced by a time lag, recall is better when other information is processed in between the first and second presentation of information. This may imply that a reflective listener recalls more information if she or he paraphrases the other person's story a while after hearing.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that more training keeps the listener on track, even if the design in the present study cannot answer whether this is an effect of enhanced RL skills or an unspecific effect of more role playing. A study of repetition and selfassessment of questions (Parkin, Wood, & Aldrich, 1988) showed that recall of orally presented information is influenced by a time lag, recall is better when other information is processed in between the first and second presentation of information. This may imply that a reflective listener recalls more information if she or he paraphrases the other person's story a while after hearing.…”
Section: Discussionmentioning
confidence: 99%
“…NS and NNS recorded different words after speech, but decreased the word inconsistency and mismatches as well as inaccurate representations with the use of text. Parkin, Wood& Aldrich (1988) explains the relationship of listening and reading as reading text motivates learners to actively process the information more than simply hearing or repetition of the information where processing task have learners to integrate the information. When experimenters asked NS when and why did you type keywords, NS testified that they typed when noticed NNS did not understand, NNS reacted after NS typed and kept typing until NNS understood, and tried to reorganize the flow of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a study of the spacing effect in verbal instruction -presenting an exposition for recall and inserting questions, repeated with different spacings, which required recall from the presentation, it was shown (Parkin, Wood, & Aldrich, 1988) that there was a clear positive effect on later recall of increasing the lag between repeated questions. Thus, in a study of the spacing effect in verbal instruction -presenting an exposition for recall and inserting questions, repeated with different spacings, which required recall from the presentation, it was shown (Parkin, Wood, & Aldrich, 1988) that there was a clear positive effect on later recall of increasing the lag between repeated questions.…”
Section: Getting Togethermentioning
confidence: 99%